Pengaruh Paham Ekstrim Wahhabi Terhadap Keharmonisan Bermasyarakat - Harahap, Mulki Al-Farizi (PT Anugerah Literasi Indomedia, 2025)
Wahhabi ideology is a school of thought in Islam that prioritizes the purification of Islamic teachings by returning to a pure understanding in accordance with the Qor’an and Hadith, as believed by the founder of this school, Muhammad bin Abd al-Wahhab. However, Wahhabi ideology is often associated with extremism, especially in relation to intolerance towards different Islamic ideologies. This article aims to analyze the influence of extreme Wahhabi ideology on social harmony, by identifying the impacts in social, cultural and religious contexts. By using a qualitative approach and content analysis, this article concludes that a Wahhabi understanding that is too rigid can potentially trigger polarization in society, especially in heterogeneous communities. A narrow understanding of religion can worsen social tolerance, thereby threatening harmony between religious communities and between fellow Muslims. Abstrak Ideologi Wahhabi merupakan aliran pemikiran dalam Islam yang mengedepankan pemurnian ajaran Islam dengan kembali pada pemahaman yang murni sesuai dengan Al-Qur’an dan Hadits, sebagaimana diyakini oleh pendiri aliran ini, Muhammad bin Abd al-Wahhab. Namun ideologi Wahhabi kerap dikaitkan dengan ekstremisme, terutama terkait intoleransi terhadap ideologi Islam yang berbeda. Artikel ini bertujuan untuk menganalisis pengaruh ideologi Wahhabi ekstrem terhadap keharmonisan sosial, dengan mengidentifikasi dampaknya dalam konteks sosial, budaya, dan agama. Dengan menggunakan pendekatan kualitatif dan analisis konten, artikel ini menyimpulkan bahwa pemahaman Wahabi yang terlalu kaku berpotensi memicu polarisasi di masyarakat, terutama pada komunitas heterogen.